Gnaq and Gna11 in the Endothelin Signaling Pathway and Melanoma - Urtatiz, Oscar; Van Raamsdonk, Catherine D. (Frontiers in Genetics, 2016)
In this article, we first briefly outline the function of G protein coupled receptors in cancer, and then specifically examine the roles of the seven transmembrane G protein coupled Endothelin B receptor (Ednrb) and the G proteins, GNAQ and GNA11, in both melanocyte development and melanoma. Ednrb plays an essential role in melanocyte development. GNAQ and GNA11 are oncogenes when mutated in certain types of melanocytic lesions, being extremely frequent in uveal melanoma, which forms from melanocytes located in the eye. Previously, we reported that in mice, Schwann cell precursor derived melanocytes colonize the dermis and hair follicles, while the inter-follicular epidermis is populated by other melanocytes. A pattern has emerged whereby melanocytes whose activities are affected by gain-of-function mutations of the Endothelin 3 ligand and Gαq/11 are the same subset that arise from Schwann cell precursors. Furthermore, the forced expression of the constitutively active human GNAQ Q209L oncogene in mouse melanocytes only causes hyper-proliferation in the subset that arise from Schwann cell precursors. This has led us to hypothesize that in Schwann cell precursor derived melanocytes, Ednrb signals through Gαq/11. Ednrb is promiscuous and may signal through other G protein alpha subunits in melanomas located in the inter-follicular epidermis.